Implementation of Access to Justice for Vulnerable Groups in the Surakarta State Court - Hanifah Febriani; Ika Rahmawati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The aim of this research is to explain: (1) the guarantee of access to justice for vulnerable groups in Indonesia; and (2) the implementation of providing access to justice for vulnerable groups in the Surakarta District Court. This study uses empirical legal research, or research that complies with normative provisions, to examine vulnerable groups' access to justice in the Surakarta District Court and identify issues related to the subjects examined from October to December 2023 as primary data. In addition, documentation studies and literature studies make use of secondary data, which can be found in a variety of sources such as books, articles, laws, news reports from the media, and so forth. The findings state that Indonesia has provided guaranteed access to justice through the speed of government institutions, ministries, and regional governments in proposing the provision of public service that are friendly to vulnerable groups, including children, women, people with disabilities, minority groups, the elderly, and the poor. Meanwhile, the Surakarta District Court has built facilities for vulnerable groups. Among them are wheelchairs, priority waiting chairs, assistive sticks, braille leaflets, courtrooms, waiting rooms, special toilets, and special paths (guide blocks, ramps, ramps) for people with disabilities. Providing access to justice is still mostly for people with disabilities.